A New Estimation Concept for Automotive Suspensions *. Issue 1 (July 2017) - Beckerman, A.; Assadian, F.; Ma, C.
Abstract: A new approach for vehicle suspension damping force and road input estimation is proposed. A Multi-Input-Multi-Output Youla Parameterization based Controller Output Observer is used. In this scheme, two measurements are required: sprung and unsprung mass acceleration. This technique is beneficial in that no assumptions are made regarding damper characteristics and dynamics. Additionally, both road input frequency content and discrete events are estimated. Two simulation examples are used to illustrate the technique: Skyhook based closed loop damping force control and road roughness coefficient estimation.